Literature Review: Efforts To Improve Creative Thinking Ability In Science Learning - Festo Kiraga (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This study aims to obtain information related to efforts to improve students' creative thinking abilities in science learning. Methodology: The review method was chosen to obtain research journals with keywords in students' creative thinking abilities in science learning with Google Scholar reference sources. Twenty five journals were reviewed based on author (year), research design, creative thinking skills, and findings. Main Findings: Based on a study of 25 articles, the application of the Project Based Learning (PjBL) learning model and the Problem Based Learning (PBL) learning model is an effort to improve creative thinking skills in science learning. Novelty/Originality of this study: This research can contribute to the world of education, especially in evaluating science learning.